Effect of Extraction Methods on Characteristic of SodiumAlginate from Brown Seaweed Sargassum fluitans - Annisa Ajeng Maharani; Amir Husni; Nurfitri Ekantari (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Alginate is a primary metabolite that is needed in food and non food industries. Alginate extractionmethod of seaweed affect on viscosity and yield of the alginate. This study aimed to determine the effect ofextraction methods on characteristic and quality of sodium alginate Sargassum fluitans and the extractioncost needed. This study used two different extraction methods which wereacid alginate method and calciumalginate method. Quality parameters observed include yield, moisture content, ash content, viscosity,pH, whiteness index, and functional group analysis, also extraction cost analysis. The results showed thatalginate extraction of S. fluitans by alginic acid method produced better sodium alginate quality than usingcalcium alginate method, but the cost higher. Sodium alginate produced by alginic acid method had highviscosity (127.17±11.50 cps) with yield 9.95±0.31%. The moisture and ash content of the product was low or9.35±0.31% and 21.88±0.41%, respectively.